2015
DOI: 10.1016/j.bmcl.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of trans- and cis-isomers of a bone-seeking agent, DO2A2P

Abstract: The macrocyclic bone-seeking agent, DO2A2P, bears a cyclen core and two pairs of peripheral phosphonate and carboxylate groups. The geometric disposition of the peripheral functionalities gives arise to a pair of geometric isomers: cis-DO2A2P and trans-DO2A2P. In order to compare the biological behavior of the isomer pair, cis-DO2A2P was synthesized. Both isomers were successfully radiolabeled with 177Lu, which might potentiate their applications in both radiotherapy and imaging of bone diseases. Through a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…6) have been studied with respect to their comparative biological behaviour. 65 Both isomers were radiolabelled with 177 Lu, for potential applications such as radiotherapy and/or imaging of bone diseases. Biological assays, such as hydroxyapatite binding, in vitro stability, and in vivo distribution, showed the pair had almost identical biological properties.…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
“…6) have been studied with respect to their comparative biological behaviour. 65 Both isomers were radiolabelled with 177 Lu, for potential applications such as radiotherapy and/or imaging of bone diseases. Biological assays, such as hydroxyapatite binding, in vitro stability, and in vivo distribution, showed the pair had almost identical biological properties.…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
“…However, previous studies mainly focused on the residue of IZM at the racemic level; no studies focused on the residue behavior of IZM at the isomer level. Different isomers of compounds have similar chemical properties, but they might show different biological behaviors in living environments . Studies have shown that the absorption, accumulation, and degradation processes of different isomers in organisms and the environment are often different. , Thus, studying the behavior of pesticides at the isomer level can better elucidate their environmental risk.…”
Section: Introductionmentioning
confidence: 99%